Advanced Concepts for Ultra-Wide-Swath SAR Imaging - Krieger, Gerhard; Gebert, Nicolas; Younis, Marwan; Bordoni, Federica; Patyuchenko, Anton; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
This paper reviews advanced multi-channel SAR system concepts for the imaging of ultra-wide swaths with high azimuth resolution. Novel system architectures and operational modes are introduced and compared to each other with regard to their performance.
DLR Import::2019-04-03